2019
DOI: 10.1371/journal.pgen.1008356
|View full text |Cite
|
Sign up to set email alerts
|

Ataxin2 functions via CrebA to mediate Huntingtin toxicity in circadian clock neurons

Abstract: Disrupted circadian rhythms is a prominent and early feature of neurodegenerative diseases including Huntington’s disease (HD). In HD patients and animal models, striatal and hypothalamic neurons expressing molecular circadian clocks are targets of mutant Huntingtin (mHtt) pathogenicity. Yet how mHtt disrupts circadian rhythms remains unclear. In a genetic screen for modifiers of mHtt effects on circadian behavior in Drosophila, we discovered a role for the neurodegenerative disease gene Ataxin2 (Atx2). Geneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 92 publications
(120 reference statements)
2
12
0
Order By: Relevance
“…Taken together with additional observations that the Atx2-cIDR is also required for the aggregation of FUS protein and C9-associated dipeptide repeats in cell culture, these results support a model in which RNP granules, perhaps by concentrating aggregation-prone proteins within membrane-less organelles, enhance the efficiency with which initial pathogenic aggregates associated with ALS/FTS can be nucleated (Becker and Gitler 2018). A more recent study of Huntington's Disease (HD) in Drosophila showed a connection between polyQ expanded Huntingtin (Htt) and Ataxin-2 (Xu et al 2019b). In Huntington's disease, pathogenic expansions occur within an endogenous polyQ domain starting at amino acid 17 of Htt.…”
Section: Introductionsupporting
confidence: 60%
See 3 more Smart Citations
“…Taken together with additional observations that the Atx2-cIDR is also required for the aggregation of FUS protein and C9-associated dipeptide repeats in cell culture, these results support a model in which RNP granules, perhaps by concentrating aggregation-prone proteins within membrane-less organelles, enhance the efficiency with which initial pathogenic aggregates associated with ALS/FTS can be nucleated (Becker and Gitler 2018). A more recent study of Huntington's Disease (HD) in Drosophila showed a connection between polyQ expanded Huntingtin (Htt) and Ataxin-2 (Xu et al 2019b). In Huntington's disease, pathogenic expansions occur within an endogenous polyQ domain starting at amino acid 17 of Htt.…”
Section: Introductionsupporting
confidence: 60%
“…A recent study on Huntington's Disease showed that overexpression of different mutant polyQ Huntington transgenes in circadian clock neurons induces circadian arrhythmicity and aggregation of Htt-polyQ in small ventral lateral neurons (sLNVs) as well as reduction in cell numbers indicative of cytotoxicity (Xu et al 2019a(Xu et al , 2019b. Reduction of Atx2 via RNAi knockdown alleviates both of these effects (Xu et al 2019b). As removal of the Atx2-cIDR has a similar effect in larval photoreceptor cells as the knock down of Atx2 in adult clock neurons, it is likely, that the formation of further aggregates and their subsequent relocalisation to the nucleus in adult flies is also inhibited.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although Fmrp upregulation did not affect translation in HD cultured striatal cells, we cannot rule out its role in HD pathogenesis. This notion is supported by evidence suggesting that deletion of Fmrp (dfmr1) suppresses the mHTT-mediated toxicity in the Drosophila model of HD 110 . In the HD brain, hypothetically, Fmrp may regulate the translation of selected mRNA transcripts involved in synaptic functions 104 , 111 , 112 .…”
Section: Discussionmentioning
confidence: 81%